Formulasi Pembuatan Shampoo dari Ekstrak Daun Sirih Cina untuk Rambut Berketombe - Yekti Rahayu; Tyas Asih Surya Mentari (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
Chinese betel leaf extract (Peperomia et al.) contains active compounds such as flavonoids, tannins, and saponins that can potentially be antimicrobial and anti-inflammatory and can be used as a hair care ingredient, especially to treat dandruff. This study aims to determine the effect of the concentration of Chinese betel leaf extract and its formulation on the characteristics of pH, foaming power, organoleptic and hedonic tests on the resulting shampoo products. Three shampoo formulations were made with variations in extract concentrations, namely 0.5%, 0.75%, and 1%, and were tested for pH, foam, organoleptic test (colour, texture, and aroma), and hedonic test (preference level). The results showed that the increase in Chinese betel leaf extract concentration tended to decrease the foaming power but produced a pH close to the ideal range for shampoo, which is 4.5-6.5. Organoleptic tests showed that the panellists accepted all formulations, although formulations with higher concentrations of extracts (1%) resulted in more robust aromas and darker colours. Hedonic tests showed that formulations with 0.75% Chinese betel leaf extract were the most preferred, with the highest aroma, colour, and texture scores. Overall, shampoo formulations with Chinese betel leaf extract have great potential to develop effective and environmentally friendly anti-dandruff products. However, further adjustments may be necessary to improve the lather's power without compromising its therapeutic benefits.